Interlinkages between climate change impacts, public attitudes, and climate action - exploring trends before and after the Paris Agreement in the EU - Schwerdtle, Patricia; Cavan, Edwige; Pilz, Lukas; Oggioni, Silvio Daniele; Crosta, Arianna; Kaleyeva, Veranika; Karim, Peshang Hama; Szarvas, Filip; Naryniecki, Tobiasz; Jungmann, Maximilian (Sustainability, 2023)
European member states have high emission reduction potential. They send a strong signal to the rest of the world with their action or inaction on climate change. Yet, within the EU, national-level climate policies (NLCP) lag behind the EU Commission’s overall climate goals. Transparency of and accountability for climate action requires an integrative perspective. Here, insights from diverse research disciplines address the following questions: How are climate impacts, public attitudes, and climate policies changing over time, and what are the interlinkages? Using three databases (Germanwatch (CCPI), European Extreme Events Climate Index (E3CI), and Eurobarometer Public Opinion Survey, 27 European countries were compared for NLCP (mitigation), climate change impacts (heat/drought), and public attitudes towards climate change (cognition/affect/conation). Differences among groups before and after the Paris Agreement were evaluated with ANOVA tests; trends and geographical differences were analysed with linear models. NLCP did not improve after the Paris Agreement, even displaying some deterioration in the eastern macro-region. Conversely, public awareness towards climate change is improving, with concern being higher in northern compared with southern countries. Heat stress is significantly related to NLCP, with increases in heat stress corresponding to improved climate policy in the northern region while worsening it in the southern region. Under worsening climate impacts, public attitudes increasingly favour climate action. However, overall policy responses are inadequate, although differences occur at the macro-regional level. The results provide granular insights into a persistent knowledge-action gap.